Innovative 3D microfluidic intestinal organoid model for assessing cadmium bioavailability in food: implications for enhanced exposure risk assessment - Yan Li; Wen Sun; Qiao Wang; Wan Shi; Yu Chen; Zhiyong Gong; Xiao Guo; Xin Liu; Yongning Wu (Food Science and Human Wellness)
Given the severe toxicity and widespread presence of cadmium (Cd) in staple foods such as rice, accurate dietary exposure assessments are imperative for public health. In vitro bioavailability is commonly used to adjust dietary exposure levels of risk factors; however, traditional planar Transwell models have limitations, such as cell dedifferentiation and lack of key intestinal components, necessitating a more physiologically relevant in vitro platform. This study introduces an innovative three-dimensional (3D) intestinal organoid model using a microfluidic chip to evaluate Cd bioavailability in food. Caco-2 cells were cultured on the chip to mimic small intestinal villi’s 3D structure, mucus production, and absorption functions. The model’s physiological relevance was thoroughly characterized, demonstrating the formation of a confluent epithelial monolayer with well-developed tight junctions (ZO-1), high microvilli density (F-actin), and significant mucus secretion (Alcian blue staining), closely resembling the physiological intestinal epithelium. Fluorescent particle tracking confirmed its ability to simulate intestinal transport and diffusion. The Cd bioavailability in rice measured by the 3D intestinal organoid model ((9.07 ± 0.21)%) was comparable to the mouse model ((12.82 ± 3.42)%) but significantly lower than the Caco-2 monolayer model ((26.97 ± 1.11)%). This 3D intestinal organoid model provides a novel and reliable strategy for in vitro assessment of heavy metal bioavailability in food, with important implications for food safety and risk assessment.